ANALYSIS DETERMINANTS OF DOMESTIC INVESTMENT (CASE STUDY IN EAST JAVA 2006-2015) - Situmorang, Kinanda Zulkarnaen (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Investment is an effort to increase economic growth within a country or region. Investment can be interpreted as an investment an individual or company to a country or region. Also, it can be divided into two, namely domestic investment and foreign investment. Domestic investment is an investment made by individual or company originating from domestic, while foreign investment is an investment made by individual or companies coming from board to a country or a region. This study aims to analyse the determinants of domestic investment in Sumatera Island in 20062015.This research uses regression method of panel data which is used to recognize determinants of domestic investment in Sumatera Island. The results obtained in this study using Random Effect Model (REM) in panel data, indicate that foreign investment (PMA) and Gross Domestic Regional product (GDRP) have a significant and positive effect on domestic investment. Labor has an insignificant result and positive effect on domestic investment, while inflation has significant result but has negative impact on domestic investment in Sumatera Island in 2006-2015Keywords: Economic Growth, Domestic Investment, Foreign Investment, Gross Domestic Regional Product, Labor, Inflation, Panel Data